2018
DOI: 10.1371/journal.pone.0197168
|View full text |Cite
|
Sign up to set email alerts
|

The impact of being bullied at school on psychological distress and work engagement in a community sample of adult workers in Japan

Abstract: ObjectiveThe aim of this study was to investigate the long-term impact of being bullied at school on current psychological distress and work engagement in adulthood among Japanese workers. We hypothesized that workers who had been bullied at school could have higher psychological distress and lower work engagement compared to those who had not been bullied.MethodsWe used data from the Japanese Study on Stratification, Health, Income, and Neighborhood (J-SHINE) project, conducted from July 2010 to February 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Table 2 shows the characteristics of the included articles. Two recently published cross-sectional studies using retrospective questions met the eligibility criteria 31,32) . Both studies examined the long-term effects of school bullying on work-related SWB among workers using secondary data.…”
Section: Characteristics and Results Of Individual Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 shows the characteristics of the included articles. Two recently published cross-sectional studies using retrospective questions met the eligibility criteria 31,32) . Both studies examined the long-term effects of school bullying on work-related SWB among workers using secondary data.…”
Section: Characteristics and Results Of Individual Studiesmentioning
confidence: 99%
“…Both studies examined the long-term effects of school bullying on work-related SWB among workers using secondary data. Of work-related SWB, one study in the United Kingdom treated evaluative well-being (ie, job satisfaction) 31) ; another study in Japan treated hedonic well-being (ie, work engagement) 32) . No studies were found that examined eudemonic well-being.…”
Section: Characteristics and Results Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over and above different sub-types of bullying, we found that psychological distress is significantly associated with self-harm, SI, and SA. Existing literature has demonstrated that there is a positive correlation between bullying experiences and psychological distress ( 58 ). Previous researchers have indicated that severe psychological distress is a major risk factor for suicidal behavior ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…School bullying can pose tremendous harm to children, including subjective well-being [5], sleeping disorder [6], depression [7], low self-esteem, anxiety [8], academic performance, suicide [9], perceived difficulties [10], confidence interval, bed wetting, headaches, tummy aches [11], psychological distress [12], mental disorders, commit crimes [13]. and so on, so it has arisen widespread concern around the world.…”
Section: Introductionmentioning
confidence: 99%